Riesgo de anemia en pobladores del distrito de Otuzco – La Libertad, marzo 2016 - Guevara Angulo, Gloria Susana (2018)
The purpose of this research was to determine the Anemia Risk of 60 inhabitants of the Otuzco district; Once signed the informed consent was applied a survey that allowed to know risk factors of anemia such as age, sex, body mass index, eating habits and an Anemia Risk Test that relates these factors to determine the risk level of the study population, performing the Hemoglobin and Hematocrit determinations, being 32% male and 68% female. The hemoglobin levels were determined by the cyanometahemoglobin method and the hematocrit levels by the microcentrifugation method in 33 inhabitants (55%) were found within the normal values and 27 residents (45%) were decreased. For the risk of anemia, the test allowed to estimate 58% of the population presents a low risk of anemia; 43% female and 15% male. The age group from 30 to 59 years old has the highest percentage of 33% low risk of anemia and the 60-94 age group slightly elevated anemia with a percentage of 15%. Finally, the level of significance p = 0.0312 was determined, which indicates that age has a significant relationship with the risk of anemia and sex with a level of significance p = 0.4636 is not significant. It is concluded that 58% of the population presents a low risk of anemia and 32% presents a slightly elevated risk